Testing the characteristics of macroprudential policies’ differential impact on foreign and domestic banks’ lending in Croatia (Public Sector Economics - submission site, 2020)
In the aftermath of 2008 financial crisis, macroprudential measures were labelled as policymakers’ best response to systemic risk and macro-financial imbalances, with their effectiveness still largely unknown due to limited use of such measures. The purpose of this paper is to clarify the potentials and limitations of these measures by evaluating both the immediate and the overall impact of macroprudential policies on banks’ lending to the non-financial private sector in Croatia. Findings reveal the divergent impact of macroprudential measures on banks’ lending with regards to their direction, i.e. tightening or loosening. Policy makers should bear this in mind when opting for a tightening of their policy stance as the reversal of that action may not match the initial impact of its introduction. Additionally, from a policymaker perspective, this paper provides potential evidence of cross-border policy spillovers, which should be taken into account in order to conduct an effective macroprudential policy.